Literasi Pemanfaatan Digital Marketing Dalam Peningkatan Usaha UMKM Di Desa Balangtanaya Kecamatan Polombangkeng Utara Kabupaten Takalar - Hajiali, Ismail; Abbas, Muhammad Abbas; Kessi, Andi Muhammad Fara; Tajuddin, Imran Tajuddin; Tasrik, Tasrik; Arrang, Hermin Arrang (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
Balangtanaya Village is one of the villages in North Polongbangkeng District, Takalar Regency, where the village has Micro, Small and Medium Enterprises has limitations in running its business in terms of introducing and selling its products in the market, the scope of sales areas is limited, and faces competition from local and other regions. This is a challenge for the development of micro, small and medium scale enterprises. This community service activity is held based on service-learning in the form of business assistance for MSME products. The stages of mentoring themselves start from the debriefing stage to monitoring. The purpose of this activity is to find out the obstacles and challenges faced by MSMEs and compile digital marketing that can support their business. Digital marketing is applied specifically in making social media suitable for MSMEs. This digital marketing is expected to develop market reach. The results of this Community Service activity show that digital marketing utilization literacy can change the way MSMEs connect with their consumers. The use of social media helps introduce, promote and market MSME products more broadly. The characteristics and needs of MSME development also cause differences in the need to apply digital marketing utilization methods through social media.